Efficiency Analysis of Fried Onion Processing Business in Kwt Kemuning, Kepahiang Regency - Emlan Fauzi; Sudarmansyah Sudarmansyah; Eko Kristanto; Wawan Eka Putra; Andi Ishak (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
Fried onion processing business is aimed at obtaining optimal profits. The problem is the price of shallot raw materials which often fluctuate so that it affects business efficiency which will have an impact on production continuity. This study aims to determine the efficiency range of fried onion processing business in KWT Kemuning, Lubur Lama Village, Bermani Ilir District, Kepahiang Regency. The study was carried out in June 2021. Data collection was conducted through interviews with the management and members of the KWT processing fried onions. The data collected is input and output data of production, selling price of fried onions, materials and tools used, and processing. Observations to observe the processing of fried onions were used to clarify the data obtained at the time of the interview. Business efficiency was analyzed by calculating the R/C ratio and the profitability of the fried onion sales business. The results showed that the R/C ratio of fried onion processing was between 1.36 - 1.78 with profitability between 35.91 - 77.61. The fried onion processing business at KWT Kemuning is already efficient. The efficiency of the processing business is largely determined by fluctuations in the price of shallots. KWT kemuning will process fried onions at a price of raw materials (shallots) between Rp. 20,000 – Rp. 30,000 per kilogram. The break-even point of fried onion production at raw material prices is around Rp. 44,539/kg assuming other variable costs are fixed. The efficiency of the fried onion processing business is strongly influenced by the price of shallots in the market.